2013
DOI: 10.15376/biores.8.4.5807-5816
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of Tannin-based Foam Preparation: Effects of Surfactant

Abstract: Three tannin-based foam formulations differing in the type of surfactant added were tested during foaming via simultaneous monitoring of the variation in temperature, foam rising rate, internal foam pressure, and dielectric polarization, the latter being a direct measure of the setting and curing of a thermosetting foam. This monitoring is an effective descriptor of the process and possible characteristics of the foam being prepared and constitutes an invaluable tool for foam formulation. The addition of a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Thus, Basso et al [11] have observed the same effect when formaldehyde is eliminated from purely tannin-furanic foam formulations. Increasing the relative proportion of surfactant extends reaction times and causes a decrease of the temperature during foaming [14], giving more controlled, but slower foaming and rising foam density (R80S). Partially replacing water by ethylene glycol (R88) induced earlier foaming, because this solvent is less effective as a heat sink.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Basso et al [11] have observed the same effect when formaldehyde is eliminated from purely tannin-furanic foam formulations. Increasing the relative proportion of surfactant extends reaction times and causes a decrease of the temperature during foaming [14], giving more controlled, but slower foaming and rising foam density (R80S). Partially replacing water by ethylene glycol (R88) induced earlier foaming, because this solvent is less effective as a heat sink.…”
Section: Resultsmentioning
confidence: 99%
“…Renewable resources can constitute an attractive alternative to conventional petrochemical resources [1][2][3]. Thus, recent work on resins derived from natural products has led to the development of rigid foams based on polyflavonoid tannins-furfuryl alcohol copolymerization, giving foams of excellent performance and characteristics [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Condensed tannins are mainly composed of polyhydroxy-flavan-3-ol and flavan-3,4-diol oligomers linked by carbon–carbon bonds between flavonoid monomer units [ 1 ]. The most used approach reported to prepare self-blowing tannin-based foams is by the acid condensation of tannins and furfuryl alcohol [ 1 ], with foam expansion driven by a blowing agent activated by the temperature increase caused by the acid self-condensation of furfuryl alcohol [ 1 , 2 , 5 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, first attempts for streamlining the batch production of thermoset foams have been carried out and applied to polyurethane (Bikard et al, 2005(Bikard et al, , 2007Bouayad et al, 2008Bouayad et al, , 2009Ireka et al, 2015;Karimi and Marchisio, 2015) and tannin-based (Basso et al, 2013d(Basso et al, , 2013b(Basso et al, , 2013c foams. In the latter case, a special commercial device initially developed for investigating the preparation of polyurethane foams, called FOAMAT® (Messtechnik, Germany), was used.…”
Section: Introductionmentioning
confidence: 99%